2020
DOI: 10.1126/sciadv.aay7608
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic-active materials enhance tissue regeneration by modulating cellular metabolic state

Abstract: Cellular bioenergetics (CBE) plays a critical role in tissue regeneration. Physiologically, an enhanced metabolic state facilitates anabolic biosynthesis and mitosis to accelerate regeneration. However, the development of approaches to reprogram CBE, toward the treatment of substantial tissue injuries, has been limited thus far. Here, we show that induced repair in a rabbit model of weight-bearing bone defects is greatly enhanced using a bioenergetic-active material (BAM) scaffold compared to commercialized po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 44 publications
0
52
0
Order By: Relevance
“…The as-prepared HMON showed speci c strong and broad peaks at 2927.32 cm -1 and 2855.28 cm -1 (attributed to -CH 2 ) [29], which represented the covalent grafting of C18PMH-mPEG chains onto the surface of HMON, compared to non-PEGylation HMON. Meanwhile, new peak at 627.03 cm -1 (attributed to Cu-S) was also observed in HMON@CuS and HMON@CuS/Gd [30].…”
Section: Resultsmentioning
confidence: 99%
“…The as-prepared HMON showed speci c strong and broad peaks at 2927.32 cm -1 and 2855.28 cm -1 (attributed to -CH 2 ) [29], which represented the covalent grafting of C18PMH-mPEG chains onto the surface of HMON, compared to non-PEGylation HMON. Meanwhile, new peak at 627.03 cm -1 (attributed to Cu-S) was also observed in HMON@CuS and HMON@CuS/Gd [30].…”
Section: Resultsmentioning
confidence: 99%
“…Through a series of experiments, both in vitro and in vivo results demonstrated that the degradation products instead of retaining the chemical or physical features of the scaffold materials may enhance bone regeneration via bioenergetic metabolism pathways. Moreover, the underlying mechanism of the promotion of repair by BAM may be that the elevated content of extracellular ATP can lead to a signaling cascade for enhanced bone repair, referring to the upregulation of purine receptors and the transduction of downstream signals via c‐Jun at the level of the gene 28 . In conclusion, the development of bioenergetic materials described here offer an uncomplicated and highly effective way to regulate the energetic demands at the early stages of bone repair.…”
Section: Other Acellular Bone Scaffold Materialsmentioning
confidence: 91%
“…Lastly, energy-driven, photothermally modified, thermodynamically controlled, and photoluminescent biodegradable materials have been prepared by researchers [28][29][30]. Tissue regeneration is dependent upon cellular bioenergetics (CBE) which, within bioenergetic-active material (BAM) scaffolds, promote mitochondrial membrane potential (ΔΨm) to provide elevated bioenergetic levels and further accelerate bone repair [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The as-prepared HMON showed specific strong and broad peaks at 2927.32 cm −1 and 2855.28 cm −1 (attributed to -CH 2 ) [29], which represented the covalent grafting of C18PMH-mPEG chains onto the surface of HMON, compared to non-PEGylation HMON. Meanwhile, new peak at 627.03 cm −1 (attributed to Cu-S) was also observed in HMON@CuS and HMON@ CuS/Gd [30].…”
Section: Preparation Characterization and In Vitro Photo-thermal Effmentioning
confidence: 98%